Effectiveness of decentralizing outpatient acute malnutrition treatment with community health workers and a simplified combined protocol: a cluster randomized controlled trial in emergency settings of Mali - López-Ejeda, Noemí; Charle-Cuéllar, Pilar; Samake, Salimata; Dougnon, Abdias Ogobara; Sánchez-Martínez, Luis Javier; Samake, Mahamadou N’tji; Bagayoko, Aliou; Bunkembo, Magloire; Touré, Fanta; Vargas, Antonio; Guerrero, Saul (Frontiers in Public Health, 2024)
Background Outpatient treatment of acute malnutrition is usually centralized in health centers and separated into different programs according to case severity. This complicates case detection, care delivery, and supply chain management, making it difficult for families to access treatment. This study assessed the impact of treating severe and moderate cases in the same program using a simplified protocol and decentralizing treatment outside health centers through community health workers (CHWs). Methods A three-armed cluster randomized controlled trial under a non-inferiority hypothesis was conducted in the Gao region of Mali involving 2,038 children between 6 and 59 months of age with non-complicated acute malnutrition. The control arm consisted of 549 children receiving standard treatment in health centers from nursing staff. The first intervention arm consisted of 800 children treated using the standard protocol with CHWs added as treatment providers. The second intervention arm consisted of 689 children treated by nurses and CHWs under the ComPAS simplified protocol, considering mid-upper arm circumference as the sole anthropometric criterion for admission and discharge and providing a fixed dose of therapeutic food for severe and moderate cases. Coverage was assessed through cross-sectional surveys using the sampling evaluation of access and coverage (SLEAC) methodology for a wide area involving several service delivery units. Results The recovery rates were 76.3% in the control group, 81.8% in the group that included CHWs with the standard protocol, and 92.9% in the group that applied the simplified protocol, confirming non-inferiority and revealing a significant risk difference among the groups. No significant differences were found in the time to recovery (6 weeks) or in anthropometric gain, whereas the therapeutic food expenditure was significantly lower with the simplified combined program in severe cases (43 sachets fewer than the control). In moderate cases, an average of 35 sachets of therapeutic food were used. With the simplified protocol, the CHWs had 6% discharge errors compared with 19% with the standard protocol. The treatment coverage increased significantly with the simplified combined program (SAM +42.5%, MAM +13.8%). Implications Implementing a simplified combined treatment program and adding CHWs as treatment providers can improve coverage while maintaining non-inferior effectiveness, reducing the expenditure on nutritional intrants, and ensuring the continuum of care for the most vulnerable children.